Clinical and Genetic Correlates of Bipolar Disorder With Childhood-Onset Attention Deficit Disorder - Nunez, Nicolas A.; Coombes, Brandon J.; Romo-Nava, Francisco; Bond, David J.; Vande Voort, Jennifer; Croarkin, Paul E.; Leibman, Nicole; Gardea Resendez, Manuel; Veldic, Marin; Betcher, Hannah; Singh, Balwinder; Colby, Colin; et al. (Frontiers in Psychiatry, 2022)
Background: Bipolar disorder (BD) with co-occurring attention deficit-hyperactivity disorder (ADHD) is associated with an unfavorable course of illness. We aimed to identify potential clinical and genetic correlates of BD with and without ADHD. Methods: Among patients with BD (N=2198) enrolled in the Mayo Clinic Bipolar Biobank we identified those with ADHD diagnosed in childhood (BD+cADHD; N=350), those with adult-onset attention deficit symptoms (BD+aAD; N=254), and those without ADHD (N=1594). We compared the groups using linear or logistic regression adjusting for age, sex, and recruitment site. For genotyped patients (N=1443), logistic regression was used to compare ADHD and BD polygenic risk scores (PRSs) between the BD groups, as well as to non-BD controls (N=777). Results: Compared to the non-ADHD BD group, BD+cADHD patients were younger, more often men and had a greater number of co-occurring anxiety and substance use disorders (all p<0.001). Additionally, BD+cADHD patients had poorer responses to lithium and lamotrigine (p=0.005 and p=0.007, respectively). In PRS analyses, all BD patient subsets had greater genetic risk for BD and ADHD when compared to non-BD controls (p<0.001 in all comparisons). BD+cADHD patients had a higher ADHD-PRS than non-ADHD BD patients (p=0.012). However, BD+aAD patients showed no evidence of higher ADHD-PRS than non-ADHD BD patients (p=0.38). Conclusions: BD+cADHD was associated with a greater number of comorbidities and reduced response to mood stabilizing treatments. The higher ADHD PRS for the BD+cADHD group may reflect a greater influence of genetic factors on early presentation of ADHD symptoms.